Contribution of anthropogenic warming to California drought during 2012–2014. Issue 16 (31st August 2015) - Williams, A. Park; Seager, Richard; Abatzoglou, John T.; Cook, Benjamin I.; Smerdon, Jason E.; Cook, Edward R.
Abstract: A suite of climate data sets and multiple representations of atmospheric moisture demand are used to calculate many estimates of the self‐calibrated Palmer Drought Severity Index, a proxy for near‐surface soil moisture, across California from 1901 to 2014 at high spatial resolution. Based on the ensemble of calculations, California drought conditions were record breaking in 2014, but probably not record breaking in 2012–2014, contrary to prior findings. Regionally, the 2012–2014 drought was record breaking in the agriculturally important southern Central Valley and highly populated coastal areas. Contributions of individual climate variables to recent drought are also examined, including the temperature component associated with anthropogenic warming. Precipitation is the primary driver of drought variability but anthropogenic warming is estimated to have accounted for 8–27% of the observed drought anomaly in 2012–2014 and 5–18% in 2014. Although natural variability dominates, anthropogenic warming has substantially increased the overall likelihood of extreme California droughts. Key Points: Warming since 1901 caused a significant trend toward drought in California Recent drought was naturally driven and modestly intensified by warming Warming has rapidly amplified the probability of severe drought